2014
DOI: 10.1371/journal.pone.0099281
|View full text |Cite
|
Sign up to set email alerts
|

Liver Resection in Hepatitis B-Related Hepatocellular Carcinoma: Clinical Outcomes and Safety in Overweight and Obese Patients

Abstract: Objective and BackgroundAlthough many studies on evaluating the safety of liver resection in obese patients have been conducted, the results remain contradictory. The aim of our study was to investigate the safety of overweight and obese patients undergoing liver resection for hepatitis B-related hepatocellular carcinoma in a large sample.MethodsIn a retrospective cohort with 1543 hepatitis B-related hepatocellular carcinoma patients, the subjects were stratified into four groups according to their body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…In another large‐scale review, Mathur et al found that obese patients had significantly higher odds of having a complication than normal‐weight patients (n=3960). However, because obesity may reportedly not influence postoperative complications in some cases, it is hoped that such cases can be analyzed in a future meta‐analysis …”
Section: Liver Surgerysupporting
confidence: 86%
See 2 more Smart Citations
“…In another large‐scale review, Mathur et al found that obese patients had significantly higher odds of having a complication than normal‐weight patients (n=3960). However, because obesity may reportedly not influence postoperative complications in some cases, it is hoped that such cases can be analyzed in a future meta‐analysis …”
Section: Liver Surgerysupporting
confidence: 86%
“…There are fewer large‐scale reviews focusing on the influences of obesity on liver surgery than on gastrointestinal surgery. The main diseases studied are hepatocellular carcinoma and liver metastasis of colorectal cancer, but there are reviews actually targeting all hepatic disorders . Table shows a summary of past studies on the effects of obesity on outcomes of liver surgery.…”
Section: Liver Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of obesity and postoperative outcomes of various surgical procedures have given inconsistent results. Some authors have reported that elevated BMI is an independent predictor of morbidity [ 31 , 32 ], whereas others have argued that complications in obese patients are directly attributable to risk factors like smoking and diabetes, while high BMI by itself is not a risk factor for postoperative complications or death, with the possible exception of increased incidence of wound infection [ 33 36 ]. These differences may reflect the use of different definitions and classifications of obesity, different ways of reporting postoperative complications, differences in surgical procedure, and lack of statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Some services keep the patient in the list after resection, while others, such as in Brazil, remove the extra score if there is resection of the nodule, and only in case of recurrence of the HCC the special situation is reestablished. Transplants in this context are known as Liver Rescue Transplantation and result in worse survival rates and high risk of relapse 15 . Chemo embolization is the gold standard treatment for patients with intermediate-stage HCC, according to the Barcelona Classification, presenting a good response in 15% to 55% of patients and an increase in the average survival from 16 to 20 months 16 .…”
Section: Discussionmentioning
confidence: 99%